PENERAPAN METODE LATIHAN INTERVAL DALAM MENINGKATKAN KECEPATAN RENANG GAYA BEBAS 50 METER - UJANG ROHMAN (Universitas Tunas Pembangunan, 2019)
The purpose of this study is to obtain a picture of the effect of interval training on the freestyle swimming speed. Limitation of this study focused on the effect of interval training on the speed of the 50m freestyle at the UKM Olahraga Renang Universitas PGRI Adibuana Surabaya. This study uses pre-experimental design using initial test followed by the provision of a new interval workout then do the final test. The population in this study is the swimmer who joined in the UKM Olahraga Renang Universitas PGRI Adibuana Surabaya, amounting to 30 players and the same sample with the population that is 30 players. The design is an experiment involving two groups: treatment group and the untreated group using the pre test and post test. Test results of the control group pre-test average of 73.02, the average post test 58.34. t-test results greater than t-table (3.84> 2.14). Comparison between pre test and post test results in the control group no significant differences, only 20:11% increase the test results. While the results of experimental tests concluded that the average pre test 58.53, the average post-test 85.85. t test results greater than t-table (2.01<2.14). Comparison between pre test and post test results on the experimental group were no significant differences. The magnitude of the effect may improve the outcome kecepaan freestyle as much as 47%. Comparison test between the control group with experimental group obtained t-count is 4.558, t-count is more than t-table (4.55> 2.04). Can be said comparison between the experimental groups with control groups and the results were no significant differences could be said after being given the treatment has the ability to swim freestyle better.Â